On the Innovative World of Care: Unveiling the Lived Experiences of Nurses in Using an Electronic Health Information System - Bingil, Jayson (Journal of Interdisciplinary Perspectives, 2024)
As healthcare systems worldwide continue to undergo digital transformation, the integration of health informatics has become pivotal in enhancing patient care, communication, and overall healthcare efficiency. The purpose of this descriptive phenomenological study was to explore and understand the experiences of staff nurses using an electronic health information system. A purposive sample of 14 senior nurses were interviewed. Using Collaizzi (1978) phenomenological method, rigor was established through application of verification, validation, and validity. From 205 significant statements, 15 cluster themes emerged. The experiences of staff nurses in employing the electronic information system included struggles during the initial encounter with the new electronic health information system, working with IT support, workflow disruption, issues regarding limited devices and internet connection, need for training, and having staff pay for errors committed. Their means of coping with the challenges of their experiences focused on recognizing workflow efficiency as perceived benefit, changes in the protocol for improvement, support from superiors and hospital management, as well as collaboration and coordination with others. The insights that staff nurses wanted to share with their peers and the nursing practice in general were personal alignment and resilience, upgrading the system, enhancing staff competency, and meeting workforce demands. Nurses adapting to a new electronic health information system echo wider healthcare's digital hurdles. Let's learn from their struggles and resilience to prioritize user-friendly designs, accessible technology, and robust training. This empowers and supports our essential nurses, paving the way for successful health informatics.